(In)aplicabilidade da prescrição intercorrente no processo do trabalho - Araújo Júnior, Vital Borba de (2016)
The statute of limitation is a legal time setting for the loss of the right of claim, due to the fact the holder didn t make use of it. The interimstatute of limitation is a kind of statute of limitation that has the dies a quo of your count of time caused by the stoppage of the process. This study will examine whether it is applicable or not, within the Labour Procedure the interimstatute of limitation. The apprehension of this research requires methodological choices that take into account the complexity of the analyzed phenomenon, which led this investigation for a foray into literature, documentary and jurisprudential analysis. Thence, was chosen a qualitative research, seeking to work with the universe of meanings drawn from the doctrines and the relevant legislation and jurisprudence. Thereby, it seek the theoretical foundations around the institute of the statute of limitations, overall the interimstatute of limitations, and then examine the divergence of understandings between the precedent 114 of the Superior Labour Court and the precedent 327, so that, finally, we can conclude for the applicability or not of the interimstatute of limitation in the Labour Procedure.